The A Mindful Learning-Based Podcast to Improve the Speaking Skills of Fourth Grade Elementary School Students - Putu Yuni Dharmayanti; Ni Ketut Desia Tristiantari; Ketut Susiani (Universitas Pendidikan Ganesha, 2026)
Elementary school students’ speaking skills remain low due to passivity, the influence of informal language from digital media, and monotonous teaching methods. This condition hinders effective communication, self-confidence, and social interaction in Indonesian language learning. This study aims to analyze and develop a mindful learning-based podcast as an innovative medium to improve students’ speaking skills, as well as to evaluate its effectiveness. The study employed a research and development approach using the ADDIE model and a one-group pretest-posttest design. The research subjects consisted of 27 students for the implementation trial, 3 teachers to assess practicality, 3 material experts, 3 media experts for validation, and 2 instrument validators. Data were collected through speaking performance tests (linguistic and non-linguistic aspects), practicality and student characteristics questionnaires, and qualitative-quantitative observations, using instruments validated through Gregory’s method. Data analysis included quantitative descriptive percentages, qualitative thematic analysis, Kolmogorov-Smirnov normality test, F-test for homogeneity, and paired t-test using SPSS 25. The results showed that the validity scores from material experts (3.85) and media experts (3.7) were categorized as highly feasible, while the practicality scores from students (90.0%) and teachers (93.3%) were categorized as highly practical. Furthermore, students’ speaking skill scores increased from 70.1 in the pretest to 83.3 in the posttest (t=8.822; df=26; p=0.000; an increase of 13.15 or 18.83%). These findings indicate that mindful learning-based podcasts are effective in improving students’ speaking skills and encourage teachers to utilize flexible audio media for active learning. The implication is that mindful learning-based podcast media can enhance students’ speaking skills while supporting holistic learning.